Impairment of microvascular angiogenesis is associated with delay in prostatic development in rat offspring of maternal protein malnutrition - Colombelli, Ketlin T. [UNESP]; Santos, Sergio A. A. [UNESP]; Camargo, Ana C. L. [UNESP]; Constantino, Flavia B. [UNESP]; Barquilha, Caroline N. [UNESP]; Rinaldi, Jaqueline C. [UNESP]; Felisbino, Sergio L. [UNESP]; Justulin, Luis A. [UNESP] (Elsevier B.V., 2017)
Experimental data demonstrated the negative impact of maternal protein malnutrition (MPM) on rat prostate development, but the mechanism behind the impairment of prostate growth has not been well understood. Male Sprague Dawley rats, borned to dams fed a normal protein diet (CTR group, 17% protein diet), were compared with those borned from dams fed a low protein diet (6% protein diet) during gestation (GLP group) or gestation and lactation (GLLP). The ventral prostate lobes (VP) were removed at post-natal day (PND) 10 and 21, and analyzed via different methods. The main findings were low birth weight, a reduction in ano-genital distance (AGD, a testosterone-dependent parameter), and an impairment of prostate development. A delay in prostate morphogenesis was associated with a reduced testosterone levels and angiogenic process through downregulation of aquaporin-1 (AQP-1), insulin/IGF-1 axis and VEGF signaling pathway. Depletion of the microvascular network, which occurs in parallel to the impairment of proliferation and differentiation of the epithelial cells, affects the bidirectional flux between blood vessels impacting prostatic development. In conclusion, our data support the hypothesis that a reduction in microvascular angiogenesis, especially in the subepithelial compartment, is associated to the impairment of prostate morphogenesis in the offspring of MPM dams. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Maternal protein malnutrition; Prostate morphogenesis; Angiogenesis; VEGF signaling; AQP1; Insulin/IGF